ARTIFICIAL NEURAL NETWORKS APPLIED TO THE MARANDU GRASS PRODUCTION ESTIMATE IN INTEGRATED SYSTEMS - Neto, Alfredo Bonini [UNESP]; Criscimani, Arthur Lopes [UNESP]; Bonini, Carolina Dos Santos Batista [UNESP]; Souza, Jessica Fernanda Dias [UNESP]; Oliverio, Gabriela Lozano [UNESP]; Baretto, Vitor Correia de Mattos [UNESP]; Andrighetto, Cristiana [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2021)
Through the MatLab software's tools, in this work a graphic interface was developed to estimate the marandu grass using artificial neural networks and the graphic properties provided by the software, aiming, on top of the assertiveness and efficiency of the estimate, the development of the interface in a way in which lay people (regarding the subject and coding), have access to the designed tool, valuing already studied User Experience concepts and being able, this way, to be used in teaching areas related to neural networks, broading the access to information through the man-machine interface.
REDES NEURALES ARTIFICIALES APLICADAS AL ESTIMADO DE PRODUCCIÓN DE HIERBA MARANDU EN SISTEMAS INTEGRADOS
REDES NEURAIS ARTIFICIAIS APLICADO À ESTIMATIVA DE PRODUÇÃO DE CAPIM MARANDU EM SISTEMAS INTEGRADOS
Keywords: Forage production; Inteligência artificial; MatLab; Prevision; User Experience